Gαq modulates the energy metabolism of osteoclasts - Chakraborty, Sushmita; Handrick, Bianca; Yu, Dayoung; Bode, Konrad A.; Hafner, Anna; Schenz, Judith; Schaack, Dominik; Uhle, Florian; Tachibana, Taro; Kamitani, Shigeki; Vogl, Thomas; Kubatzky, Katharina F. (Frontiers in Cellular and Infection Microbiology, 2023)
The bacterial protein toxin Pasteurella multocida toxin (PMT) mediates RANKL-independent osteoclast differentiation. Although these osteoclasts are small, their resorptive activity is high and they efficiently destroy the nasal turbinate bones of pigs. Analysis of the proteome of classical, RANKL-induced and toxin-derived osteoclasts showed that PMT induces the upregulation of metabolic pathways. This includes strong glycolytic activity, increased expression of GLUT1 and upregulation of the mTOR pathway. As OxPhos components are also expressed more efficiently, cells display increased mitochondrial respiration. We found that the heterotrimeric G protein Gq plays a central role in this hypermetabolic cell activation. Gq triggers mitochondrial relocalisation of pSerSTAT3 and an increase in OPA1 expression. This seems to be caused by a direct interaction between STAT3 and Opa1 resulting in enhanced mitochondrial respiration. Overexpression of Gq mimicked this hypermetabolic phenotype and resulted in higher glycolytic and mitochondrial activity as well as increased bone resorptive activity. Rheumatoid arthritis patients show an increase in Gnaq expression especially in the synovial fluid, suggesting that Gq is a target of pathophysiological relevance.